Joel’s self-redemption in the unnatural narrative structure of Charlie Kaufman’s Eternal Sunshine of the Spotless Mind (2004) - Mohd Said, Nur Aainaa Amira; Ali Termizi, Arbaayah; Awang, Mohammad Ewan (Universiti Putra Malaysia Press, 2021)
This essay discusses the significance of the unnatural narrative structure in Charlie Kaufman’s screenplay Eternal Sunshine of the Spotless Mind (2004). Oftentimes, the screenplay’s reverse chronology is studied as a backdrop to accentuate its thematic values of personal identity and memory. However, this study argued that the reverse narrative was caused by the protagonist’s self-redemption journey. To achieve this objective, two components of Kenneth Burke’s dramatism theory, dramatistic pentad and guilt-redemption cycle were utilized. The pentadic analysis explored the connection between the main characters’ actions and motives with the structure of the text while also interpreting the implication of its reverse narrative from the framework of guilt-redemption cycle. From the findings, the study affirms that the screenplay’s unnatural narrative structure i.e. reverse chronology integrally founded the narrative structure of the text by representing Joel’s regret in a sequence of guilt-redemption cycle. As a result, it showcases the versatility of dramatism theory as one of the analytical tools for narrative studies particularly on the unnatural narrative structure of screenplay texts.